Evaluation of the efficacy of pyrantel-oxantel for the treatment of soil-transmitted nematode infections - Albonico, Marco (Trans R Soc Trop Med Hyg, 2002)
A randomized controlled trial comparing the efficacy of pyrantel-oxantel (10 mg/kg) with mebendazole (500 mg) was performed on 1329 schoolchildren aged 6-9 years on Pemba Island in September-October 2000 to evaluate alternative single-dose drugs for regular treatment of intestinal nematode infections. Both mebendazole and pyrantel-oxantel were very effective in eliminating Ascaris lumbricoides infection, inducing cure rates of more than 96% and reducing the mean egg counts by more than 95%. Both drugs had a moderate efficacy against Trichuris trichiura infection, but pyrantel-oxantel had a higher cure rate (31.5% vs. 23.3%, P < O.Ol), though the reductions in egg counts did not differ significantly and were more than 80%. Pyrantel-oxantel and mebendazole had a similar, poor efficacy in curing hookworm infections and had a moderate effect in reducing the egg counts by 67% and 68%, respectively. Pyrantel-oxantel (10 mg/kg) offers a valuable alternative to mebendazole as a single-dose treatment for the control of intestinal nematode infections in children in endemic areas of sub-Saharan Africa, due to its comparable efficacy, its low cost and its suitability for use in young children.